EFFICACY AND SAFETY OF CELL-BASED THERAPIES FOR STRESS URINARY INCONTINENCE: A SYSTEMATIC REVIEW (CAHIERS MAGELLANES-NS, 2024)
This review article investigates the efficacy and safety of cell-based therapies in treating stress urinary incontinence (SUI), which significantly impacts the quality of life for millions of women globally. With a prevalence rate of 10%–40%, SUI often results from anatomical defects such as hypermobile urethra and intrinsic sphincter deficiency. Traditional conservative treatments, including behavioral therapy and pelvic floor exercises, may offer initial relief, but invasive surgical interventions carry potential complications and varying success rates. Emerging evidence highlights the promise of stem cell therapy, particularly utilizing muscle-derived stem cells (MDSCs) and adipose-derived stem cells (ADSCs), in regenerating urinary sphincter function. Preclinical and clinical trials indicate substantial improvement in incontinence scores, sphincter contractility, and overall quality of life following autologous stem cell injections, with reported cure rates ranging from 59% to 90.5%. Importantly, these interventions demonstrated favorable safety profiles with minimal adverse effects. This review consolidates existing literature on cell-based therapies for SUI, underscoring their potential as a transformative approach in the management of this condition. Future studies and controlled trials are necessary to further elucidate their long-term outcomes and optimize treatment protocols.